2017
DOI: 10.1248/bpb.b17-00457
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Has a Synergistic Anticancer Effect with Cisplatin <i>via</i> Inhibiting Fanconi Anemia Group D2 Protein Monoubiquitination in Hepatocellular Carcinoma Cells

Abstract: Cisplatin is an anticancer agent and induces DNA interstrand cross-links (ICLs). ICLs activate various signaling processes and induce DNA repair pathways, including the Fanconi anemia (FA) pathway. FA complementation group D2 (FANCD2) is monoubiquitinated in response to DNA damage, leading to activation of the DNA double-strand-break repair protein, RAD51. Caffeine increases the anticancer activity of cisplatin by inhibiting DNA repair; however, details of the mechanism remain unclear. We investigated the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…They enhance the anticancer activity of oxaliplatin in human colon, breast, and ovarian cancers by inhibiting DNA synthesis resulting from alternation of the pyrimidine pathway . Caffeine exerted a synergistic anticancer effect with cisplatin in hepatocellular carcinoma cells by inhibiting DNA repair resulting from the decreased monoubiquitination of the FANCD2 protein . Estrogen sensitizes prostate cancer cells LNCaP to cisplatin possibly by increasing the expression of HMG1 by methylation of estrogen receptor-α .…”
Section: Platinum-based Combinations Based On the Underlying Molecula...mentioning
confidence: 99%
See 1 more Smart Citation
“…They enhance the anticancer activity of oxaliplatin in human colon, breast, and ovarian cancers by inhibiting DNA synthesis resulting from alternation of the pyrimidine pathway . Caffeine exerted a synergistic anticancer effect with cisplatin in hepatocellular carcinoma cells by inhibiting DNA repair resulting from the decreased monoubiquitination of the FANCD2 protein . Estrogen sensitizes prostate cancer cells LNCaP to cisplatin possibly by increasing the expression of HMG1 by methylation of estrogen receptor-α .…”
Section: Platinum-based Combinations Based On the Underlying Molecula...mentioning
confidence: 99%
“…51 Caffeine exerted a synergistic anticancer effect with cisplatin in hepatocellular carcinoma cells by inhibiting DNA repair resulting from the decreased monoubiquitination of the FANCD2 protein. 52 Estrogen sensitizes prostate cancer cells LNCaP to cisplatin possibly by increasing the expression of HMG1 by methylation of estrogen receptor-α. 53 PARP inhibitors have also been reported to enhance the anticancer activity of platinum drugs by influencing the repair of DNA damage.…”
Section: Platinum-based Combinations Based Onmentioning
confidence: 99%
“…Patients with a disrupted structure of FANCD2, mainly carriers of Fanconi anemia, have higher risk of cancer development [64,65]. The most frequent cancer types related to FANCD2 are ovarian [66], hepatic [67], lung [68], breast cancer [69] and leukemia [70]. FANCD2 co-localizes with RAD51a following DNA damage is an indication that FANCD2 and RAD51a share roles in DNA repair through physical interactions [16,17,71].…”
Section: In Silico Model For the Rad51a Interaction With Fancd2mentioning
confidence: 99%
“…For example, it was shown that caffeine increases the antiproliferative activity and apoptosis caused by cisplatin in cultured cells. 36,37 Thus, the alkaloid decreases the cell viability when combined with cisplatin. 36,37 None of these effects were usually found when caffeine was used alone in cell culture assays, showing that they are really a result of the combination with cisplatin.…”
Section: ■ Introductionmentioning
confidence: 99%
“…36,37 Thus, the alkaloid decreases the cell viability when combined with cisplatin. 36,37 None of these effects were usually found when caffeine was used alone in cell culture assays, showing that they are really a result of the combination with cisplatin. 37 Nevertheless, this opened up questions related to these findings concerning the real role of the cellular machinery in such a process and the physical chemistry of the interactions involved.…”
Section: ■ Introductionmentioning
confidence: 99%